Concussed athletes walk slower than non-concussed athletes during cognitive-motor dual-task assessments but not during single-task assessments 2 months after sports concussion: a systematic review and meta-analysis using individual participant data. Issue 2 (22nd July 2019) - Büttner, Fionn; Howell, David R; Ardern, Clare L; Doherty, Cailbhe; Blake, Catherine; Ryan, John; Catena, Robert; Chou, Li-Shan; Fino, Peter; Rochefort, Coralie; Sveistrup, Heidi; Parker, Tonya; et al.
Abstract : Objectives: To determine whether individuals who sustained a sports concussion would exhibit persistent impairments in gait and quiet standing compared to non-injured controls during a dual-task assessment . Design: Systematic review and meta-analysis using individual participant data (IPD). Data sources: The search strategy was applied across seven electronic bibliographic and grey literature databases: MEDLINE, EMBASE, CINAHL, SportDISCUS, PsycINFO, PsycARTICLES and Web of Science, from database inception until June 2017. Eligibility criteria for study selection: Studies were included if; individuals with a sports concussion and non-injured controls were included as participants; a steady-state walking or static postural balance task was used as the primary motor task; dual-task performance was assessed with the addition of a secondary cognitive task; spatiotemporal, kinematic or kinetic outcome variables were reported, and; included studies comprised an observational study design with case–control matching. Data extraction and synthesis: Our review is reported in line with the Preferred Reporting Items for Systematic review and Meta-Analyses-IPD Statement. We implemented the Risk of Bias Assessment tool for Non-randomised Studies to undertake an outcome-level risk of bias assessment using a domain-based tool. Study-level data were synthesised in one of three tiers depending on the availability and quality of data: (1) homogeneous IPD; (2) heterogeneous IPD and (3) aggregate data for inclusion in a descriptive synthesis. IPD were aggregated using a 'one-stage', random-effects model. Results: 26 studies were included. IPD were available for 20 included studies. Consistently high and unclear risk of bias was identified for selection, detection, attrition, and reporting biases across studies. Individuals with a recent sports concussion walked with slower average walking speed (χ 2 =51.7; df=4; p<0.001; mean difference=0.06 m/s; 95% CI: 0.004 to 0.11) and greater frontal plane centre of mass displacement (χ 2 =10.3; df=4; p=0.036; mean difference −0.0039 m; 95% CI: −0.0075 to −0.0004) than controls when evaluated using a dual-task assessment up to 2 months following concussion. Summary/conclusions: Our IPD evidence synthesis identifies that, when evaluated using a dual-task assessment, individuals who had incurred a sports concussion exhibited impairments in gait that persisted beyond reported standard clinical recovery timelines of 7–10 days. Dual-task assessment (with motion capture) may be a useful clinical assessment to evaluate recovery after sports concussion. Protocol pre-registration: This systematic review was prospectively registered in PROSPERO CRD42017064861.